2018
DOI: 10.1093/ntr/nty140
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Tobacco Exposure Decrease After Smokers Switch to an E-Cigarette or Nicotine Gum

Abstract: This is the first study to report changes in nicotine delivery and biomarkers of tobacco exposure following a short-term product switch from CCs to either an EC or NG in a controlled environment. The study shows that nicotine exposure decreased in both groups but was maintained closer to CC smoking with the EC groups. Biomarkers of tobacco combustion decreased to similar levels in both EC and gum groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 36 publications
9
63
0
2
Order By: Relevance
“…Concerns regarding the heterogeneity of e-liquid composition in terms of variable nicotine concentrations and carcinogenic constituents led the Food and Drug Administration to extend regulatory authority to include these products in 2016. In this review, several studies reported the e-cigarette device voltage and resistance under typical usage conditions [9,25,35,36], while other studies attempted to standardize the e-liquid used [23,31] and frequency of vaping to reduce variability [1,28,35]. Moreover, metabolites of carcinogens in urine may be directly related to the intensity of e-cigarette usage, including time to last use prior to obtaining the urine specimen, although few studies controlled for this variable [1,26,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Concerns regarding the heterogeneity of e-liquid composition in terms of variable nicotine concentrations and carcinogenic constituents led the Food and Drug Administration to extend regulatory authority to include these products in 2016. In this review, several studies reported the e-cigarette device voltage and resistance under typical usage conditions [9,25,35,36], while other studies attempted to standardize the e-liquid used [23,31] and frequency of vaping to reduce variability [1,28,35]. Moreover, metabolites of carcinogens in urine may be directly related to the intensity of e-cigarette usage, including time to last use prior to obtaining the urine specimen, although few studies controlled for this variable [1,26,28].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 22 included studies, four were randomized controlled trials [9,[23][24][25], six were multi-institutional studies [8,[24][25][26], 10 were single-institutional studies, two analyses were of the US Population Assessment of Tobacco and Health [27,28], and one was an analysis of the National Health and Nutrition Examination Survey [29]. In addition, two pairs of studies reported results from common datasets [7,9,23,30] and four were sponsored by the tobacco or ecigarette industry [9,23,25,31]. Aggregation of the 22 studies produced an overall sample size of 1259 study participants, where individual sample study sizes ranged from 6 to 280.…”
Section: Study Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…For the current review, 60 relevant publications with comparisons were identified. 6,28,29,[44][45][46][49][50][51][52][53][54][55][56][57]59,[61][62][63][64][65][66][67][68][69][70][71][84][85][86]89,[93][94][95][96][97][98][99][100][101][102]105,[107][108][109][110][125][126][127][128][129]…”
Section: Cigarettes Per Day (Cpd)mentioning
confidence: 99%